Application of electrochemical noise technique to monitor carbon steel corrosion under sand deposit - Hou, Y.; Aldrich, Chris; Lepkova, K.; Suarez, L.; Kinsella, B. (2017)
© 2017 by NACE International. The corrosion process of carbon steel in the presence of silica sand deposit in chloridecontaining solution at 30 °C was monitored by use of electrochemical noise (EN). Noise resistance calculated from EN was compared with the polarization resistance obtained from conventional corrosion monitoring techniques, such as linear polarization resistance (LPR) and electrochemical impedance spectroscopy (EIS). Recurrence quantification analysis (RQA) was employed to characterize the current noise data associated with different corrosion types and the extracted variables were used for UDC process monitoring. After tests, the corroded steel surfaces were examined using a 3D profilometry to gather information about localized defects. The results demonstrated that electrochemical noise associated with recurrence quantification analysis is a useful tool for monitoring localized corrosion of under deposit corrosion.